Diverse evolutionary pathways shaped 5S rDNA of species of tribe Anemoneae (Ranunculaceae) and reveal phylogenetic signal. (20th July 2016) - Mlinarec, Jelena; Franjević, Damjan; Bočkor, Luka; Besendorfer, Višnja
Abstract : Anemone sensu lato (including Pulsatilla and Hepatica ), tribe Anemoneae (Ranunculaceae), is arranged into two subgenera, Anemone and Anemonidium, with basic chromosome numbers x = 8 and x = 7, respectively. We elucidated the level of divergence of 5S rDNA unit arrays between the subgenera, determined intra‐individual and interspecific sequence variation and tested 5S rDNA phylogenetic signal in revealing the origin of polyploid species. High intra‐individual nucleotide diversity and the presence of 5S rDNA unit array length variants and pseudogenes indicate that weak homogenization forces have shaped 5S rDNA in the investigated species. Our results show that 5S rDNA evolved through two major changes: diversification of 5S rDNA into two lineages, one with long (subgenus Anemone ) and one with short 5S rDNA unit arrays (subgenus Anemonidium ); and subsequent contraction and expansion of 5S rDNA unit arrays. Phylogenetic analysis based on 5S rDNA supports the hypothesis that A. parviflora could be a parental species and donor of the subgenome D to the allopolyploids A. multifida (BBDD) and A. baldensis (AABBDD). In A. baldensis interlocus exchange possibly occurred, followed by subsequent replacement of the 5S rDNA from subgenome D with those from subgenome B. Here we present evidence that both models, concerted and birth‐and‐death evolution, were probably involved in the evolution of the 5S rDNA multigene family in subgenera Anemone and Anemonidium .